2011
DOI: 10.1249/mss.0b013e318210783c
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Functional Magnetic Resonance Imaging Cortical Activation with Cross Education to an Immobilized Limb

Abstract: Handgrip strength training of the free limb attenuated strength loss during unilateral immobilization. The maintenance of strength in the immobilized limb via the cross-education effect may be associated with increased motor cortex activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
68
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 42 publications
5
68
0
2
Order By: Relevance
“…Recently, several trials have shown that the strength of an immobilized arm can be maintained when the contralateral limb undergoes resistance training during the immobilization period (Farthing et al. 2009, 2011; Magnus et al. 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several trials have shown that the strength of an immobilized arm can be maintained when the contralateral limb undergoes resistance training during the immobilization period (Farthing et al. 2009, 2011; Magnus et al. 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It is, however, equivocal as to whether cross education to an immobilized limb attenuates atrophy with studies showing no effect (Farthing et al. 2011) or a relative preservation of muscle thickness (Farthing et al. 2009; Magnus et al.…”
Section: Discussionmentioning
confidence: 99%
“…As the neurophysiological evidence for cross-education is demonstrating that the nervous system is responding to unilateral training, the logical step for further investigation is the clinical environment (such as immobilisation or un-weighting of a limb). Initial studies in upper limb have shown positive results (Farthing et al , 2011Magnus et al 2010) and it appears likely that the same protocol can be used to benefit people with lower limb injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Recent physiological studies, with the quantification of some of the cardiorespiratory responses to predominantly static exercises using small and different muscle groups and with different percentages of maximal voluntary strength, have contributed to a better understanding of the mechanisms associated with IHT and similar exercises 14,15,[33][34][35][36][37] . Nevertheless, when these physiological data, respecting the methodological differences and small samples involved, are compared with our results, one can identify a 13 .…”
Section: Discussionmentioning
confidence: 99%